TANGGUNG JAWAB WARGA BELAJAR PENDIDIKAN KESETARAAN PAKET C DI PKBM PRIMATRAIN PEKANBARU - Sari, Ratna; Wilson, Wilson; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on responsibility residents learn equality education package C inPKBM Primatrain Pekanbaru. Because the responsibility of the study is awareness of people learn to work and responsibilities as a resident studying for them to study Pusat Kegiatan Belajar Masyarakat (PKBM) PrimatrainPekanbaru. Formulation problems in this research was how high responsibility residents learn equality education package C in PKBM Primatrain Pekanbaru?. The purpose of this research is to find the responsibility of residents learn equality education package C in PKBM Primatrain Pekanbaru. Population in this study as many as 40 people learn. Then the researcher determine samples from 40 people for research and 20 people for testing somewhere else, with using a technique sampling jenuh. An instrument data collection that is chief with 50 a statement and if the trial live 46 a statement valid for in made instrument research. Through data analysis of the quantitative descriptive analysis. So, the research results show that responsibility residents learn equality education package C in PKBM Primatrain Pekanbaru, Categorized High, with the highest indicators obligation students look at of the value of a percentage (SB+B) 75%. It means residents learn very aware of their obligations and responsibilities as the learner / residents learn evidenced by coming perfection. educational institutions at the correct time. While indicators duty students with a value of a percentage (SB+B) 73%. It means residents learn package c aware of the task as a students in PKBM With do their tasks at home in an earnest manner.Key words: TheResponsibility, The responsibility of residents learn paket C